A numerical and theoretical study on the seismic behaviour of yielding cantilever walls. Issue 5 (9th July 2018) - Conti, R.; Caputo, G.
Abstract : This paper provides an interpretation of the dynamic behaviour of yielding cantilever walls, regarding which open issues still remain about the applicability of the Mononobe–Okabe theory and the possible occurrence of phase shift between the maximum soil thrust and the inertia forces into the system, which both affect the seismic design of these structures. To this end, the predictions of a pseudostatic limit equilibrium/analysis model are combined with the results of an extensive numerical study, with both pseudostatic and dynamic analyses performed under real earthquakes and simple input motions. Numerical outcomes show that the maximum soil thrust on the stem and the maximum bending moment are always in phase and occur when the inertia forces are away from the backfill. The proposed model provides a good prediction of the maximum internal forces induced by the earthquake. It is shown that the possible activation of plastic mechanisms within the system, in the form of either sliding or bearing failure, makes the critical acceleration a key ingredient for the seismic design of cantilever walls, controlling both the maximum internal forces and the magnitude and trend of final displacements. Numerical and theoretical findings are used to provide suggestions for the seismic design of cantilever walls.